Molecular and Epidemiological Characterization of ESBL-producing from Captive Wild Birds in Zoological Gardens in Nigeria - Ridwan Olamilekan Adesola; Adetolase Azizat Bakre; Abimbola Olumide Adekanmbi; Bamidele Nyemike Ogunro; Oluwaseun Adeolu Ogundijo; Abdulafees Hamzat; Delower Hossain; Moses Aimanosi Aribana; Luqman Adeola Balogun (Environmental Health Insights)
Aim: This study aimed to characterize ESBL-producing E. coli isolates obtained from apparently healthy captive wild birds from selected zoological gardens in Nigeria. Materials and Methods: A total of 121 freshly deposited faecal samples were collected from captive wild birds in seven major zoological gardens and pooled into 50 samples. The samples were screened for the presence of E. coli . The isolates obtained were tested against a panel of antibiotics and screened for ESBL production using the double disc synergy test (DDST). Primer-specific PCR was used to detect the carriage of ESBL genes ( bla CTX-M , bla TEM and bla SHV ) by the isolates. Results: A total of 26 ESBL-producing E. coli isolates (52%, n = 26/50) were obtained from the pooled faecal samples of captive wild birds. The highest resistance rate to antibiotics was observed with amoxicillin-clavulanate (88.5%), while the lowest resistance rate was observed with fosfomycin (3.8%). The isolates had Multiple Antibiotic Resistance Index (MARI) values ranging from 0.1 to 0.8 across the tested antibiotics. Approximately 65.4% of the isolates carried bla CTX-M , while bla TEM and bla SHV were detected in 15.4% and 34.6% of the isolates, respectively. Conclusion: This study revealed a significant prevalence of ESBL-producing E. coli in captive wild birds in Nigeria and highlighted the need to institute control measures in zoological gardens to prevent the transmission of antibiotic resistance.